(untitled) (Scientific journal of the Fergana State University, 2025)
This study uses a magnetic polymer nanocomposite to examine the photocatalytic degradation of paracetamol in pharmaceutical wastewater. The transformation of paracetamol into its toxic metabolite N-acetyl-p-benzoquinone imine (NAPQI) and subsequent products (e.g., p-benzoquinone and hydroxylated compounds) was found to elevate oxidative stress and bioaccumulation risks in aquatic ecosystems. Under UV irradiation (λ=365 nm), Fe₃O₄/PPE-1 degraded paracetamol with 85±5% efficiency within 160 minutes, retaining 90% activity after 5 cycles due to its magnetic recyclability. The study proposes a new approach to sustainable wastewater treatment and demonstrates the potential of using solar resources in line with Uzbekistan’s “Green Economy” strategy.